Last visit was: 19 Jul 2024, 22:48 It is currently 19 Jul 2024, 22:48
Close
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Close
Request Expert Reply
Confirm Cancel
SORT BY:
Date
Tags:
Show Tags
Hide Tags
Math Expert
Joined: 02 Sep 2009
Posts: 94421
Own Kudos [?]: 642406 [33]
Given Kudos: 86332
Send PM
Senior Manager
Senior Manager
Joined: 03 Sep 2012
Posts: 356
Own Kudos [?]: 971 [0]
Given Kudos: 47
Location: United States
Concentration: Healthcare, Strategy
GMAT 1: 730 Q48 V42
GPA: 3.88
WE:Medicine and Health (Health Care)
Send PM
Alum
Joined: 12 Aug 2015
Posts: 2271
Own Kudos [?]: 3197 [0]
Given Kudos: 893
GRE 1: Q169 V154
Send PM
Manager
Manager
Joined: 24 Mar 2015
Status:love the club...
Posts: 217
Own Kudos [?]: 112 [0]
Given Kudos: 527
Send PM
Re: A sequence is given by the rule an = |a_(n-2)| - |a(n-1)| [#permalink]
Bunuel wrote:

Winner:

yogeshwar007

Official Explanation:

Answer is C

While we spend a lot of time honing the skill of translating English into algebra, there is sometimes great comfort to be gained in a sequence problem through doing precisely the reverse. The general rule for this sequence is that we derive each term based on the two terms that precede it – specifically by subtracting the absolute value of the previous term from the absolute value of the “pre-previous” one.

So \(a_3 = |a_1| - |a_2|\), and \(a_4 = |a_2| - |a_3|\), and \(a_5 = |a_3| - |a_4|\), and so on. We are told that the sequence begins 0, 3, ..., so we can derive that:

\(a_3 = |a_1| - |a_2| = |0| - |3| = 0 - 3 = -3\).
Then \(a_4 = |a_2| - |a_3| = |3| - |-3| = 3 - 3 = 0\).
Then \(a_5 = |a_3| - |a_4| = |-3| - |0| = 3 - 0 = 3\).

As soon as we’ve seen \(a_4\) and \(a_5\) turn out to be 0 and 3 consecutively, we know that the next number to show up in the sequence will be identical to the number that showed up after the last time we saw 0 and 3 appear consecutively (i.e. as \(a_1\) and \(a_2\)) — so \(a_6\) will be identical to \(a_3\), so -3. So we have established the pattern 0, 3, -3, 0, 3, -3, ... for our sequence.

Every time we finish a complete cycle within the sequence, the sum returns to 0 (since 0 + 3 + -3 = 0). We finish a cycle after every third entry (i.e. after the third, the sixth, the ninth, and so on), so we will have done so (and returned our running sum to 0) with \(a_{99}\). \(a_{100}\) will then add itself (0) to that sum, and \(a_{101}\) will add itself (3) onto that. So we will land at a sum of 3 for \(s_{101}\).


hi Bunuel

The sum of numbers until a99 will be zero, that's okay, but how can a100 be zero..?

At a99 the cycle is complete, the new cycle begins at a100, then how ..?

please say to me

I have tried this way
99 is a multiple of 3, so when the cycle is complete a99 corresponds to a3, and 100 is multiple of 4, so 100 corresponds to a4 ending at 0, so a101 is equal to 3

please help me work it out

thanks in advance, man
Math Expert
Joined: 02 Sep 2009
Posts: 94421
Own Kudos [?]: 642406 [0]
Given Kudos: 86332
Send PM
Re: A sequence is given by the rule an = |a_(n-2)| - |a(n-1)| [#permalink]
Expert Reply
gmatcracker2017 wrote:
Bunuel wrote:

Winner:

yogeshwar007

Official Explanation:

Answer is C

While we spend a lot of time honing the skill of translating English into algebra, there is sometimes great comfort to be gained in a sequence problem through doing precisely the reverse. The general rule for this sequence is that we derive each term based on the two terms that precede it – specifically by subtracting the absolute value of the previous term from the absolute value of the “pre-previous” one.

So \(a_3 = |a_1| - |a_2|\), and \(a_4 = |a_2| - |a_3|\), and \(a_5 = |a_3| - |a_4|\), and so on. We are told that the sequence begins 0, 3, ..., so we can derive that:

\(a_3 = |a_1| - |a_2| = |0| - |3| = 0 - 3 = -3\).
Then \(a_4 = |a_2| - |a_3| = |3| - |-3| = 3 - 3 = 0\).
Then \(a_5 = |a_3| - |a_4| = |-3| - |0| = 3 - 0 = 3\).

As soon as we’ve seen \(a_4\) and \(a_5\) turn out to be 0 and 3 consecutively, we know that the next number to show up in the sequence will be identical to the number that showed up after the last time we saw 0 and 3 appear consecutively (i.e. as \(a_1\) and \(a_2\)) — so \(a_6\) will be identical to \(a_3\), so -3. So we have established the pattern 0, 3, -3, 0, 3, -3, ... for our sequence.

Every time we finish a complete cycle within the sequence, the sum returns to 0 (since 0 + 3 + -3 = 0). We finish a cycle after every third entry (i.e. after the third, the sixth, the ninth, and so on), so we will have done so (and returned our running sum to 0) with \(a_{99}\). \(a_{100}\) will then add itself (0) to that sum, and \(a_{101}\) will add itself (3) onto that. So we will land at a sum of 3 for \(s_{101}\).


hi Bunuel

The sum of numbers until a99 will be zero, that's okay, but how can a100 be zero..?

At a99 the cycle is complete, the new cycle begins at a100, then how ..?

please say to me

I have tried this way
99 is a multiple of 3, so when the cycle is complete a99 corresponds to a3, and 100 is multiple of 4, so 100 corresponds to a4 ending at 0, so a101 is equal to 3

please help me work it out

thanks in advance, man


It's very easy. The sequence is:

{0, 3, -3} {0, 3, -3} {0, 3, -3} {0, 3, -3} ...

Notice that if n is a multiple of 3, so a3, a6, ..., a99, then it's -3. The next terms, so a4, a7, ..., a100 are 0.
Manager
Manager
Joined: 24 Mar 2015
Status:love the club...
Posts: 217
Own Kudos [?]: 112 [0]
Given Kudos: 527
Send PM
Re: A sequence is given by the rule an = |a_(n-2)| - |a(n-1)| [#permalink]
Bunuel wrote:
gmatcracker2017 wrote:
Bunuel wrote:

Winner:

yogeshwar007

Official Explanation:

Answer is C

While we spend a lot of time honing the skill of translating English into algebra, there is sometimes great comfort to be gained in a sequence problem through doing precisely the reverse. The general rule for this sequence is that we derive each term based on the two terms that precede it – specifically by subtracting the absolute value of the previous term from the absolute value of the “pre-previous” one.

So \(a_3 = |a_1| - |a_2|\), and \(a_4 = |a_2| - |a_3|\), and \(a_5 = |a_3| - |a_4|\), and so on. We are told that the sequence begins 0, 3, ..., so we can derive that:

\(a_3 = |a_1| - |a_2| = |0| - |3| = 0 - 3 = -3\).
Then \(a_4 = |a_2| - |a_3| = |3| - |-3| = 3 - 3 = 0\).
Then \(a_5 = |a_3| - |a_4| = |-3| - |0| = 3 - 0 = 3\).

As soon as we’ve seen \(a_4\) and \(a_5\) turn out to be 0 and 3 consecutively, we know that the next number to show up in the sequence will be identical to the number that showed up after the last time we saw 0 and 3 appear consecutively (i.e. as \(a_1\) and \(a_2\)) — so \(a_6\) will be identical to \(a_3\), so -3. So we have established the pattern 0, 3, -3, 0, 3, -3, ... for our sequence.

Every time we finish a complete cycle within the sequence, the sum returns to 0 (since 0 + 3 + -3 = 0). We finish a cycle after every third entry (i.e. after the third, the sixth, the ninth, and so on), so we will have done so (and returned our running sum to 0) with \(a_{99}\). \(a_{100}\) will then add itself (0) to that sum, and \(a_{101}\) will add itself (3) onto that. So we will land at a sum of 3 for \(s_{101}\).


hi Bunuel

The sum of numbers until a99 will be zero, that's okay, but how can a100 be zero..?

At a99 the cycle is complete, the new cycle begins at a100, then how ..?

please say to me

I have tried this way
99 is a multiple of 3, so when the cycle is complete a99 corresponds to a3, and 100 is multiple of 4, so 100 corresponds to a4 ending at 0, so a101 is equal to 3

please help me work it out

thanks in advance, man


It's very easy. The sequence is:

{0, 3, -3} {0, 3, -3} {0, 3, -3} {0, 3, -3} ...

Notice that if n is a multiple of 3, so a3, a6, ..., a99, then it's -3. The next terms, so a4, a7, ..., a100 are 0.



thanks Bunuel

if started from "0", a99 will correspond to "-3" and will sum to "0", then a100 will have value "0" and 101 will be "3"

now it is very clear to me, thank to you again, man

can you please, however, provide me some questions of this kind for further practice?
thanks 8-)
Math Expert
Joined: 02 Sep 2009
Posts: 94421
Own Kudos [?]: 642406 [0]
Given Kudos: 86332
Send PM
Re: A sequence is given by the rule an = |a_(n-2)| - |a(n-1)| [#permalink]
Expert Reply
gmatcracker2017 wrote:
thanks Bunuel

if started from "0", a99 will correspond to "-3" and will sum to "0", then a100 will have value "0" and 101 will be "3"

now it is very clear to me, thank to you again, man

can you please, however, provide me some questions of this kind for further practice?
thanks 8-)


12. Sequences


Manager
Manager
Joined: 24 Mar 2015
Status:love the club...
Posts: 217
Own Kudos [?]: 112 [0]
Given Kudos: 527
Send PM
Re: A sequence is given by the rule an = |a_(n-2)| - |a(n-1)| [#permalink]
Bunuel wrote:
gmatcracker2017 wrote:
thanks Bunuel

if started from "0", a99 will correspond to "-3" and will sum to "0", then a100 will have value "0" and 101 will be "3"

now it is very clear to me, thank to you again, man

can you please, however, provide me some questions of this kind for further practice?
thanks 8-)


12. Sequences




thanks a lot bunu 8-)
User avatar
Intern
Intern
Joined: 06 Jun 2024
Posts: 6
Own Kudos [?]: 1 [0]
Given Kudos: 0
Location: United States
Send PM
Re: A sequence is given by the rule an = |a_(n-2)| - |a(n-1)| [#permalink]
To solve for s101s101​, the sum of the first 101 terms of the sequence defined by an=∣an−2∣−∣an−1∣an​=∣an−2​∣−∣an−1​∣ with initial conditions a1=0a1​=0 and a2=3a2​=3, we need to compute the sequence up to a101a101​ and then find the cumulative sum.

Let's calculate the sequence step by step:

a1=0a1​=0
a2=3a2​=3
a3=∣a1∣−∣a2∣=∣0∣−∣3∣=0−3=−3a3​=∣a1​∣−∣a2​∣=∣0∣−∣3∣=0−3=−3
a4=∣a2∣−∣a3∣=∣3∣−∣−3∣=3−3=0a4​=∣a2​∣−∣a3​∣=∣3∣−∣−3∣=3−3=0
a5=∣a3∣−∣a4∣=∣−3∣−∣0∣=3−0=3a5​=∣a3​∣−∣a4​∣=∣−3∣−∣0∣=3−0=3
a6=∣a4∣−∣a5∣=∣0∣−∣3∣=0−3=−3a6​=∣a4​∣−∣a5​∣=∣0∣−∣3∣=0−3=−3

Continuing this process until a101a101​:

The sequence alternates between 0, 3, -3 with a repeating cycle every 3 terms: 0,3,−3,0,3,−3,…0,3,−3,0,3,−3,….

To find s101s101​, we need to calculate how many complete cycles of 3 terms fit into 101 terms:

There are ⌊1013⌋=33⌊3101​⌋=33 complete cycles.
In each cycle, the sum 0+3−3=00+3−3=0.

Therefore, the sum of these 33 cycles is 33×0=033×0=0.

Additionally, we need to include any remaining terms beyond these complete cycles:

There are 101−33×3=2101−33×3=2 remaining terms.

The terms a100a100​ and a101a101​ correspond to the sequence elements where the cycle restarts, which are −3−3 and 00 respectively.

So, s101=0+(−3)+0=−3s101​=0+(−3)+0=−3.

Therefore, s101s101​ is −3−3​.­
GMAT Club Bot
Re: A sequence is given by the rule an = |a_(n-2)| - |a(n-1)| [#permalink]
   1   2 
Moderator:
Math Expert
94421 posts